Satisfaction towards virtual consultation services and its associated factors among health care providers in government health clinics in Selangor - Razak, Ihsan Abdul (2023)
Background: Virtual consultation services have been implemented by the Ministry of Health since 2019 to complement current healthcare service delivery in government health clinics in Malaysia. While the services have been proven to benefit the patients, little is known about the satisfaction of healthcare providers who run the services. This study utilizes the extended Technology Acceptance Model to evaluate the satisfaction of health care providers and identify the associated factors to further improve the services. Objectives: To determine the proportion of health care providers (HCP) who were satisfied with the virtual consultation services and identify the associated factors that contribute to HCP’s satisfaction towards virtual consultation services. Methodology: A cross sectional study was conducted in 42 government health in Selangor using a questionnaire adopted from the extended Technology Acceptance Model. A total of 137 health care providers from various categories responded to the online survey. Data were analysed using descriptive statistic, simple and multiple logistic regression. Result: Majority of respondents (72.3%) were satisfied with the virtual consultation services with mean score of 14.47 (3.391). Two factors were found to have significant association with health care providers’ satisfaction which were perceived usefulness (AdjOR 9.396, 95% CI: 3.196 to 27.625) and behavioural intention (AdjOR 8.311, 95% CI: 2.494 to 27.694). Conclusion: Perceived usefulness and behavioural intention of health care providers strongly predict satisfaction towards virtual consultation services in government health clinics in Selangor. Therefore efforts should be directed towards improving satisfaction level of health care providers by addressing these factors to ensure sustainability of the services in the future and to continue benefit the patients.